An evaluation of the recruitment and retention strategy of professional nurses in the Mpumalanga Department of Health : a case of Ehlanzeni District, South Africa - Chiloane, Goodman Richard (My University, 2017)
Recruitment and retention of nurses remain one of the challenges globally and locally as the system is unable to attract new staff and failing to retain existing ones. This study was undertaken to investigate the number of nurses leaving the Mpumalanga Department of Health and whether the available recruitment and retention strategy puts the province into the competitive advantage. The qualitative and quantitative methods of data collection were utilised during the investigations. Both the qualitative and quantitative analysis proved that a number of nurses were leaving the public service influenced by factors such as salary, workload, accommodation for nurses, working conditions and lack of resources. The findings further revealed that the recruitment and retention strategy of the Department was poorly implemented and therefore leaving the province at a risk of losing more professional nurses. The main recommendation in this study was that the Department of Health in Mpumalanga needs to ensure that adequate funds are available for the proper implementation of the recruitment and retention strategy. The proper implementation of the strategy will help in addressing the factors that were discussed and agreed to by other studies to be contributing immensely in nurses’ turnover in the province.
Thesis (MPA.) -- University of Limpopo, 2017
Keywords: Recruitment; Retention; Professional nurses; Nurses -- Recruiting -- South Africa -- Mpumalanga; Nurses -- Employment -- South Africa -- Mpumalanga; Employees -- Recruiting; Employees retention -- South Africa -- Mpumalanga